Epidemiological study of some intestinal parasites affecting humans in Al-Najaf Al-Ashraf province - Sahar J. alhassany (Kufa Journal for Nursing Sciences)
Background: The study revealed the Percentage of human infection with intestinal parasites in (246) patients came to AL Sadder general hospital & AL_Monadhara general hospital in Najaf Governorate between January 2011 to December 2011. The total number of I intestinal parasitic was 124 (85.4%) which included: 61 (88%) of Amoebiasis cases, 42 (73.6%) of Giardiasis cases, 21 (35%) of Ascariasis Cases. The infection was generalized and not related to age group, sex occupation or socioeconomic state.